Safety and Effectiveness of a Novel Integrated Angiography System for Continuous Guidance and Flushing in Diagnostic Cerebral Catheter Angiography: A Randomized Controlled Trial - Kwon, Boseong; Yoon, Jong-Tae; Choi, Yun Hyeok; Jeong, Soo; Kim, Byung Jun; Choi, Joon Ho; Hwang, Sun Moon; Lee, Deok Hee; Song, Yunsun (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: The guided angiography system, an integrated angiography system, enables continuous guidance and flushing during diagnostic procedures. A guidewire provides guidance by remaining inside the catheter during contrast injection into tortuous vessels. While its feasibility was demonstrated in a retrospective study, this randomized controlled trial aims to evaluate its safety and effectiveness.MATERIALS AND METHODS: This single-center, single-blind, randomized controlled trial was conducted from September 2021 to June 2022. Patients with unruptured intracranial aneurysms were enrolled and randomly assigned to either the guided or the conventional group. Primary outcomes were procedural time and serious adverse events. Secondary outcomes included catheterization success, adverse events, fluoroscopy time, fluoroscopy dose, and image quality.RESULTS: A total of 200 participants (mean age, 59 [SD, 10 years], 71% women) were randomized into the guided (n = 100) and the conventional (n = 100) groups. The guided group demonstrated shorter procedural times compared with the conventional group (18.3 [SD, 9.2] versus 21.3 [SD, 8.1] minutes, P < .001). There were no serious adverse events in either group, and adverse events were similar. Catheterization success rates were similar between the guided and conventional groups (93.9% versus 96.8%, P = .226). However, the guided angiography system backed up more catheterization failures from the conventional angiography system, but not vice versa (57.1% versus 11.1%, P = .003). Among catheterization successes, the guided group achieved shorter fluoroscopy time (7.0 versus 7.7 minutes, P = .033) and lower fluoroscopy dose (466.8 versus 566.5 μGy·m2, P = .015). Regarding imaging quality, clinical acceptability was comparable between the guided and conventional groups (95.3% versus 95.5%, P = .781).CONCLUSIONS: The guided angiography system offers a simple and effective alternative for diagnostic cerebral conventional angiography, with reduced radiation exposure and a favorable safety profile.AEadverse event